VD_FINDINFO ML / 2014 / 167 vom 10. Juli 2014 - VD Tribunal cantonal (2014)
SIGNATURE, RECONNAISSANCE DE DETTE, REPRÉSENTANT, AVOCAT, HONORAIRES | 82 LP, 105 al. 2 CPC (CH), 106 al. 1 CPC (CH), 95 al. 3 let. b CPC (CH), 20 al. 2 TDC, 6 TDC